Identification of a human Th1-like IFNγ-secreting Treg subtype deriving from effector T cells - Venigalla, Ram Kumar Chowdary; Guttikonda, Padmaja Jayathi; Eckstein, Volker; Ho, Anthony Dick; Sertel, Serkan; Lorenz, Hanns-Martin; Tretter, Theresa (Journal of autoimmunity, 2012)
Characteristics and function of effector T-cells with regulatory properties (induced Treg, “iTreg”) in humans are ill defined. Here we report that a proportion of activated, initially CD4(+)CD25(−)CD127(+) effector T-cells from human peripheral blood can convert into T-cells with regulatory activity while concomitantly secreting IFNγ. Upon short-term culture in vitro these cells expressed a panel of common Treg markers, including FOXP3, CD25, GITR, HLA-DR and CTLA-4 in parallel with the Th1-specific transcription factor T-bet. Despite their own IFNγ secretion they effectively suppressed IFNγ secretion in effector T cells in parallel with inhibition of their proliferation. Highly purified IFNγ(+)iTreg shared many functional properties with nTreg: Their suppressive activity was antigen-independent, contact-mediated and cytokine-independent. Of note, in contrast to nTreg an inhibitor of TGF-β1 signalling promoted the proliferation of IFNγ(+)iTreg, without abrogating their suppressive function. In addition in vivo in tonsils of patients with chronic tonsillitis an IFNγ-secreting subpopulation of the CD4(+)CD25(−)CD127(+)CD45RA(−) memory T helper cell population was detected, which exhibited regulatory properties as well. Our results support the existence of Th1-like adaptive Tregs in humans that express a robust regulatory phenotype, comparable to nTreg and at the same time share characteristics of Th1 cells. According to our in vitro data IFNγ(+)iTreg can emerge from activated effector T cells and downregulate Th1-mediated immune responses, supporting the hypothesis of effector T cell plasticity as a means for proper initiation and self regulation of inflammatory processes. This report characterizes a new subpopulation of human adaptive regulatory T-cells that derive from effector Th-cells and concomitantly express Th1-specific T-bet and IFNγ with Foxp3.
Gesehen am 15.10.2018